The Roman Occupation of Britain and Its Legacy - Jackson, Rupert M. Sir (Bloomsbury Publishing Plc, 2020)
Cover page -- Halftitle page -- Title page -- Copyright page -- Dedication -- CONTENTS -- ILLUSTRATIONS -- PREFACE -- CHAPTER 1 INTRODUCTION AND BACKGROUND -- 1. INTRODUCTION -- 2. A BRIEF ACCOUNT OF THE ROMAN EMPIRE -- 3. THE ROMAN ARMY -- 4. HOW DO WE KNOW WHAT HAPPENED? -- (i) Contemporaneous historians -- (ii) Official records -- (iii) Archaeological evidence -- CHAPTER 2 BRITAIN IN THE IRON AGE -- 1. INTRODUCTION -- 2. THE IRON AGE -- 3. CONTACT WITH THE MEDITERRANEAN WORLD -- 4. BRITISH COMMUNITIES DURING THE LATE IRON AGE -- (i) South- east England -- (ii) Dorset and the Midlands -- (iii) The West Country and Wales -- (iv) The north -- 5. ROME'S PERCEPTION OF BRITAIN IN THE LATE IRON AGE -- CHAPTER 3 THE FIRST INVASIONS: JULIUS CAESAR -- 1. INTRODUCTION -- 2. THE INVASION IN 55 BC -- 3. THE INVASION IN 54 BC -- 4. REVIEW OF CAESAR'S CAMPAIGNS IN BRITAIN -- CHAPTER 4 THE INVASION OF SOUTHERN BRITAIN: THE EMPEROR CLAUDIUS -- 1. INTRODUCTION AND BACKGROUND -- 2. RELATIONS BETWEEN BRITAIN AND ROME -- 3. CLAUDIUS' INVASION IN AD 43 -- 4. CONSOLIDATION OF ROMAN CONTROL -- (i) South- west England -- (ii) South- east England -- (iii) The Midlands -- CHAPTER 5 BRITAIN IN THE MID-FIRST CENTURY -- 1. ADMINISTRATION AND FINANCES OF THE EMERGENT PROVINCE -- 2. THE CAMPAIGNS AGAINST WALES -- 3. BRITISH ECONOMY AND SOCIETY IN THE MID-FIRST CENTURY -- CHAPTER 6 BOUDICA'S REBELLION AND ITS AFTERMATH -- 1. INTRODUCTION -- 2. BACKGROUND TO THE REBELLION: ROMAN REPRESSION AND GREED -- 3. BOUDICA STRIKES BACK (AD 60-61) -- 4. THE ROMANS PREVAIL -- 5. AFTERMATH -- CHAPTER 7 THE FLAVIAN PERIOD -- 1. INTRODUCTION -- 2. IMPROVING THE INFRASTRUCTURE AND ADMINISTRATION OF THE PROVINCE -- 3. CERIALIS' CAMPAIGN AGAINST THE BRIGANTES -- 4. CAMPAIGNS IN WALES: FRONTINUS AND AGRICOLA -- 5. AGRICOLA'S CAMPAIGNS IN THE NORTH -- 6. THE PERIOD AFTER AGRICOLA.